The Theory of Nationalisation - Katzarov, Konstantin. author. aut Link
392 p. 4 illus.
Keywords: In this book Professor Katzarov has made the first comprehensive study 0/ nationalisation /rom the legal point 0/ view. The author's knowledge 0/ European languages, in addition to his mother tongue 0/ Bulgarian, has enabled him to draw on material/rom England, France, the U.s.S.R. and the other communist countries 0/ Eastern Europe, and many countries 0/ Asia and Latin America. The book ranges widely in another sense. Professor Katzarov is a jurist in the best Continental tradition in that his work does not spring /rom a narrow technical outlook, but is a synthesis 0/ historical, philo sophic, political, economic and legal elements. Thus, he shows the way in which the constitutional and legal /ramework 0/ nationalisation has been in/luenced by extra-legal elements. It is difficult to imagine a legal scholar trained in one 0/ the Common Law countries producing a work as broadly conceived; and this is one 0/ several reasons why the publication 0/ an English edition is welcome.